2009
DOI: 10.1039/b817063k
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase photocatalytic oxidation of acrylonitrile

Abstract: Photocatalytic oxidation (PCO) of acrylonitrile (AN) on titanium dioxide in the gaseous phase was studied. AN readily undergoes photocatalytic degradation in a gas-solid system by using TiO(2) Degussa P25. The AN PCO volatile products, visible in the infrared spectra, included nitrogen dioxide, nitrous oxide, carbon dioxide, water, hydrogen cyanide and carbon monoxide. Longer contact time resulted in deeper oxidation of AN with decreasing hydrogen cyanide and increasing nitrogen dioxide content. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…Photocatalytic decomposition was investigated for many types of gaseous pollutants, such as volatile organic compounds (VOCs; see references 223–229), and decomposition frequently follows a Langmuir–Hinshelwood type rate law.…”
Section: Properties Of Tio2 and Photocatalytic Mechanismsmentioning
confidence: 99%
“…Photocatalytic decomposition was investigated for many types of gaseous pollutants, such as volatile organic compounds (VOCs; see references 223–229), and decomposition frequently follows a Langmuir–Hinshelwood type rate law.…”
Section: Properties Of Tio2 and Photocatalytic Mechanismsmentioning
confidence: 99%
“…The oxidation reaction rates usually depend on temperature increasing with the temperature growth. At the same time adsorption is deteriorated with the temperature increase, compensating the reaction rate improvement having PCO reactions often insensitive towards temperature changes as observed previously with AN PCO at P25 [18]. The 'reaction rate-adsorption' balance at sulphated P25 appears to be dramatically negatively influenced by the temperature decrease practically zeroing its performance.…”
Section: The Impact Of Temperature and Residence Time On Pco Performancementioning
confidence: 62%
“…The products formed on sulphated TiO 2 differ from the ones formed on Degussa P25 [18] in part of HNCO, the peaks of which appear in the volatile products spectra (Fig. 5).…”
Section: Pco By-productsmentioning
confidence: 94%
See 1 more Smart Citation
“…The PCO of acrylonitrile has not been widely studied in the literature. Krichevskaya et al [42] studied the gas phase degradation of acrylonitrile by using Degussa P25 under UV irradiation at concentrations ranging from 10 to 100 ppm at temperatures ranging from 50 to 130°C. They observed that degradation rates were improved at longer contact times and lower concentrations and decreased at higher temperatures.…”
mentioning
confidence: 99%